SAMHD1, positively regulated by KLF4, suppresses the proliferation of gastric cancer cells through MAPK p38 signaling pathway. Issue 19 (2nd October 2022) - Chen, Zhangming; Jiang, Zhe; Meng, Lei; Wang, Ye; Lin, Minggui; Wei, Zhijian; Han, Wenxiu; Ying, Songcheng; Xu, Aman
ABSTRACT: SAMHD1 was reported to be related with the development of tumors, while its function in gastric cancer (GC) has not been elucidated yet. Here, we investigated the role and mechanism of SAMHD1 in regulating the proliferation of GC, as well as the mechanism of its expression regulation. Our results revealed that SAMHD1 was downregulated in GC tissues and cell lines, which was correlated with tumor size, depth of invasion and TNM stage. Overexpression of SAMHD1 inhibited the proliferation, clone formation, DNA synthesis and cell cycle progression, while knockdown of SAMHD1 promoted the proliferation of GC cells in vitro and vivo. Meanwhile, SAMHD1 inhibited the activation of MAPK p38 signaling pathway. Moreover, SB203580, as a MAPK p38 inhibitor, could reverse the proliferation and activation of MAPK p38 signaling pathway caused by knockdown of SAMHD1 in GC cells. Additionally, transcription factor Krüppel-like factor 4 (KLF4) bound to the core promoter of SAMHD1, increasing its transcriptional expression in GC cells. In conclusion, SAMHD1 suppressed the proliferation of GC through negatively regulating the activation of MAPK p38 signaling pathway and was upregulated by KLF4 in GC cells.